Dari kesenjangan menjadi jembatan: Transformasi kepemimpinan kristiani intergenerasional - Purba, Paskah Parlaungan (Sekolah Tinggi Teologi Pelita Bangsa, Jakarta, 2025)
Intergenerational gaps often pose a significant challenge within the church and Christian leadership context. Differences in values, perspectives, communication styles, and ministry preferences can create barriers that hinder unity, mission effectiveness, and the spiritual continuity from one generation to the next. This article analyzes the nature and impact of intergenerational gaps in Christian leadership and proposes a transformative approach to convert these